KLASIFIKASI KEMAMPUAN LAHAN PADA TANAH BERBAHAN INDUK TUFA TONDANO SEPANJANG JALUR JALAN BELANG-RATAHAN - Kamagi, Yani; Lengkong, Jeanne (EUGENIA, 2015)
ABSTRACT This study aimed to determine the class of land capability, land using, and conservation technique which could be applied at Tondano tuff derived soils along Belang-Ratahan road. The results showed that, four  classes of  land capability, were: a)  class III at 100 m (Watulinei), 200 m, and 300 m (Wawali) above sea level; b) class IV at 400 m (Lowu II) and 600 m (Pangu) above sea level; c) class VI at 700 m above sea level (Pangu), and  d) class VIII at 500 m and 800 m above sea level (Pangu). Most of the land using were not suitable, yet and there were no soil and water conservation technique applied, yet. Only at 700 m and 800 m above sea level that have been used suitable  as the nature reserved. Keywords: land capability, Tondano tuff